2015
DOI: 10.2174/1566524015666150921105453
|View full text |Cite
|
Sign up to set email alerts
|

ER Stress and Autophagy

Abstract: Eukaryotic cells respond to various types of stresses caused by changes in the extracellular environment. Intracellular factors, such as the accumulation of misfolded proteins in the endoplasmic reticulum (ER), also cause stress and activate the unfolded protein response (UPR), which induces the expression of chaperones and proteins involved in the recovery process. However, if the stress is excessive or sustained, and ER function cannot be restored, the UPR triggers apoptosis, thereby removing the affected ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
112
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(116 citation statements)
references
References 0 publications
4
112
0
Order By: Relevance
“…Over-activated or prolonged ER stress can initiate apoptosis through two principal UPR receptors IRE-1 and PERK [16, 17]. In HG-treated podocytes, we found that the level of CHOP, Grp78 and the phosphorylated PERK at Thr389 was highly enhanced compared to NG- and MN-treated cells (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Over-activated or prolonged ER stress can initiate apoptosis through two principal UPR receptors IRE-1 and PERK [16, 17]. In HG-treated podocytes, we found that the level of CHOP, Grp78 and the phosphorylated PERK at Thr389 was highly enhanced compared to NG- and MN-treated cells (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…ER stress is also named as unfolded protein response (UPR) since it mainly deal with unfolded and/or miss-folded proteins [16, 17]. In the conditions of over-activated and/or prolonged ER stress, the role of UPR changes from promoting cellular survival to committing the cell to an apoptotic pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Autophagy is particularly important in postmitotic cells where it functions to remove damaged components that would otherwise accumulate and harm the cell. 20,21 This concept has been borne out in numerous model systems, and dysfunctional autophagy has been implicated in neurodegenerative diseases such as Alzheimer and Huntington diseases. [22][23][24] In rod photoreceptors the light-/dark-induced translocation of phototransduction proteins is thought to regulate light sensitivity whereby the concentration of transducin and ARR/arrestin in the photoreceptor OS is the critical factor.…”
Section: Discussionmentioning
confidence: 99%